Development of Fun-Trastic Physical Activity Model: An Innovative Approach for Children Aged 9–10 Years - Nurrafi'u, Gizalias Kusnanda; Akhiruyanto, Andry (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2024)
The importance of physical activity in enhancing student engagement in the learning process has prompted the development of the Fun-Trastic model, a fun, traditional, music, and energetic physical activity designed for the early childhood phase. This study aims to evaluate the effectiveness of the Fun-Trastic model in engaging students, measuring their enthusiasm and preferences, and assessing its feasibility in educational contexts. A Research and Development (R&D) approach was employed, consisting of three stages: model trial, expert validation, and student preference evaluation. The participants in the study were 9-10-year-old elementary school students from Central Java and the Special Region of Yogyakarta. Data collection involved a Likert-scale questionnaire administered after students performed the Fun-Trastic activities, with a focus on measuring engagement, enjoyment, and intensity levels. Results showed that students found the Fun-Trastic activity to be highly enjoyable and engaging, with positive responses regarding their enthusiasm and participation. Additionally, the activity was considered appropriately challenging without causing excessive exertion, indicating its potential as an effective physical activity model for elementary school students. The study concluded that Fun-Trastic could be a valuable addition to physical education programs, promoting student engagement without overwhelming them.